How electromyography readings from the human forearm are made cryptic, trivial, or non-trivial information for use in synthetic systems - Bani Hashim, Ahmad Yusairi; Fu, Zinvi; Jamaludin, Zamberi; Mohamad, Imran Syakir (IACSIT Press, Singapore, 2015)
The success of reading potentials generating from human muscle activities is evident that proves that the human body’s neural system is naturally electronics. Now, modern engineering is accepting it as one field of engineering science. Due to this, the concept of a cyborg is beginning to realize as products such as exoskeletons and neuroprostheses. The object of this work, however, is to view from a different perspective as to how this is beneficial to the functions beyond the mentality of today’s applications. We hypothesized that the recorded potentials from muscle activities may be regarded similar as to the signals that jump between synapses in the biological neurons. We suggest that these signals, instead of mere electrical in nature, their waveforms might include emotion characteristics from uniquely combined muscle activities and feeling. The system codes the signals where the newly created information may be made cryptic, trivial, or nontrivial depending on how they are going to be utilized in the synthetic systems. So that the artificial system could sense, for instance, the emotion of the human host.